Measuring Engineering Design Self-Efficacy - Carberry, Adam R. (Tufts Archival Research Center, 2005)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Math, Science, Technology, and Engineering Education. Abstract: The purpose of this study is to take an initial step in the measurement of conative measures, by documenting the development and validation of a new instrument to assess engineering design self-efficacy. Self-efficacy is a motivational construct regarding an individuals belief or judgment of their capability to organize and execute courses of action for a given domain-specific task (Bandura, 1986, 1997). Self-efficacy influences behaviors in accordance with perceived abilities for a specific task. The task of interest for this study will be engineering design. Engineering design is the process used to devise a system, component, or process to meet a need. The concept was chosen because of its importance in the field of engineering (Auyang, 2004).